Embryonic exposure to model naphthenic acids delays growth and hatching in the pond snail Lymnaea stagnalis. (February 2017) - Johnston, Christina U.; Clothier, Lindsay N.; Quesnel, Dean M.; Gieg, Lisa M.; Chua, Gordon; Hermann, Petra M.; Wildering, Willem C.
Abstract: Naphthenic acids (NAs), a class of structurally diverse carboxylic acids with often complex ring structures and large aliphatic tail groups, are important by-products of many petrochemical processes including the oil sands mining activity of Northern Alberta. While it is evident that NAs have both acute and chronic harmful effects on many organisms, many aspects of their toxicity remain to be clarified. Particularly, while substantive data sets have been collected on NA toxicity in aquatic prokaryote and vertebrate model systems, to date, nothing is known about the toxic effects of these compounds on the embryonic development of aquatic invertebrate taxa, including freshwater mollusks. This study examines under laboratory conditions the toxicity of NAs extracted from oil sands process water (OSPW) and the low-molecular weight model NAs cyclohexylsuccinic acid (CHSA), cyclohexanebutyric acid (CHBA), and 4- tert -butylcyclohexane carboxylic acid (4-TBCA) on embryonic development of the snail Lymnaea stagnalis, a common freshwater gastropod with a broad Palearctic distribution. Evidence is provided for concentration-dependent teratogenic effects of both OSPW-derived and model NAs with remarkably similar nominal threshold concentrations between 15 and 20 mg/L and 28d EC50 of 31 mg/L. In addition, the data provide evidence for substantial toxicokinetic differences between CHSA, CHBA and 4-TBCA. Together, our study introduces Lymnaea stagnalis embryonic development as an effective model to assay NA-toxicity and identifies molecular architecture as a potentially important toxicokinetic parameter in the toxicity of low-molecular weight NA in embryonic development of aquatic gastropods. Highlights: NAs impede pond snail ( Lymnaea stagnalis ) embryonic development. OSPW-derived and model NAs cause concentration-dependent reduction in snail hatching. NA molecular architecture affects in ovo toxicokinetic characteristics.